Utilization of Ferry as a Support of The Community Economy on The Alalak River Based as a Learning Resource on Social Studies - Muhammad Rezky Noor Handy; Abdurrahim Abdurrahim; Bambang Subiyakto; Syaharuddin Syaharuddin; Muhammad Adhitya Hidayat Putra; Helmi Akmal; Dhimas Pratama Nindya Putra Sari (Social Studies Conference Proceedings, 2022)
The utilization of ferries on the banks of the Alalak river, which is still used by the community to carry out daily activities, produces various kinds of social activities, which are then used as learning resources to provide the understanding and make it easier for students to understand the aims and objectives of learning. This study aims to describe how the use of ferries as a means of crossing the community on the banks of the Alalak river, as well as what economic activities occur in the process and whether the use of ferries on the banks of the Alalak river can be used as a source of social studies learning. This thesis uses descriptive qualitative research where this study aims to describe the use of ferries on the banks of the Alalak river as a social studies learning resource. The location of this research is between North Alalak Village and East Berangas Village. Data collection techniques used are Observation, Interviews, and Documents. Analysis of the data used, namely data reduction based on research objectives and data presentation. Test the validity of the data with extended observations, member checks, and triangulation. The results of this study explain the existence of economic activities in using ferries on the banks of the Alalak river. The forms of economic activity are Production, Distribution, and Consumers. This economic activity is then used as a contextual learning resource to make it easier for students to understand what the teacher explains in learning because it uses examples around their environment.